A first-principles study on the electronic property and magnetic anisotropy of ferromagnetic CrOF and CrOCl monolayers. (26th April 2021) - Xu, Chunyan; Zhang, Jing; Guo, Zexuan; Zhang, Siqi; Yuan, Xiaoxi; Wang, Lingrui
Abstract: Two-dimensional ferromagnetic materials with large perpendicular magnetic anisotropy (PMA) hold great potential in realizing low critical switching current, high thermal stability and high density nonvolatile storage in magnetic random-access memories. Our first-principles calculations reveal that CrOF and CrOCl monolayers (MLs) are two-dimensional (2D) ferromagnetic semiconductors with out-of-plane magnetic easy axis, and PMAs of CrOF and CrOCl MLs are mainly contributed by Cr atoms. The magnetic anisotropy of CrOF and CrOCl MLs can be controlled and enhanced by applying biaxial strain. Tensile strain can further enhance PMAs of CrOF and CrOCl MLs by 82.9% and 161.0% higher than those of unstrained systems, respectively. In addition, appropriate compressive strain can switch the magnetic easy axis of CrOF and CrOCl MLs from out-of-plane direction to in-plane direction. The semiconductor natures of CrOF and CrOCl MLs robust against biaxial strain, the band gaps of these systems under biaxial strain are in the range of 1.26 eV to 2.40 eV. By applying biaxial strain, the Curie temperatures of CrOF and CrOCl MLs increase up to 282 K and 163 K, respectively. These tunable properties suggest that CrOF and CrOCl MLs have great application potentials for magnetic data storage.